Diagnosis of covert coarctation of the aorta in adolescents - Wei, Luyao; Hu, Shijun; Gong, Xueyang; Ahemaiti, Yiliya; Zhao, Tianli (Frontiers in Pediatrics, 2023)
Objectives: By reviewing the diagnostic process for adolescents with coarctation of the aorta (CoA) in our institution, we analyzed the reasons for delayed diagnosis of CoA. We also proposed a diagnostic protocol to improve the detection rate of CoA. Methods: In this retrospective study, we included 48 patients aged 12–18 years who were diagnosed with CoA in our hospital from January 2000 to November 2022. Clinical data from involved cases in local hospitals and our institution were collected. Results: All patients had blood pressure (BP) measurements in upper and lower extremities in our institution. They all had hypertension, 29 (60.4%) of whom had known histories of the same. BP in the upper limbs of 47 (97.9%) patients was ≥ 20mmHg higher than that in the lower limbs, and BP in the upper limb of 1 (2.1%) patient was greater than 0 and less than 20mmHg than that in the lower limb. Echocardiography (ECHO) was performed in all patients, computed tomography (CT) or magnetic resonance imaging (MRI) was performed in 44 patients (91.7%). There were 38 (79.2%) patients who visited local hospitals. Among them, a total of 20 (52.6%) patients had their right upper extremity BP measured, 18 (47.4%) only had their left upper extremity BP measured, and 16 (42.1%) had their lower extremity BP measured. ECHO was performed in 27 (56.2%) patients and CT/MRI was performed in 18 (37.5%) patients. The detection rate for CT/MRI was 100%, and those of ECHO were 72.9% and 18.5% at our institution and a local hospital, respectively. Forty-eight (100%) and 23 (60.5%) patients were detected in our institution and local hospitals (P ＜0.0001). Conclusion: We recommend measuring BP in the bilateral upper extremities. Measurement of BP in the lower extremities is recommended if hypertension is diagnosed. MRI/CT is recommended when BP in the upper extremity is greater than that in the lower extremity.